Comparison of Effectiveness of Calcipotriol Versus Steroids In The Treatment of Chronic Hand Eczema - Shah, Sabahat; Seemab Khan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate efficacy of calcipotriol versus topical corticosteroids ointment in treatment of chronic hand eczema (CHE).Study Design: Quasi-experimental.Place and Duration of Study: Department of Dermatology, Pakistan Naval Ship (PNS) Shifa, Karachi, Pakistan, from May to Nov 2023.Methodology: Patients with CHE, who met the inclusion criteria, were recruited and divided into two groups, with one group receiving calcipotriol and the other was given topical corticosteroids twice daily, for 2 months. Hand Eczema and Severity Index (HECSI) scores and patient self-assessment conducted at baseline, second, sixth, and eighth week after enrollment, were used to measure efficacy. During the treatment, adverse reactions were also assessed.Results: A statistically significant improvement was noted in HECSI compared to baseline, beginning in second week of therapy (p0.05). Almost all individuals improved by more than 50.00% by the end of the study duration. Moderate scaling was the most frequent side effect of calcipotriol, whereas moderate dryness was the most frequent negative effect of topical corticosteroids.Conclusion: Calcipotriol ointment was noted to have the same therapeutic efficacy as topical corticosteroids in the treatment of CHE.